Host Genetics and Antiviral Immune Responses in Adult Patients With Multisystem Inflammatory Syndrome - Ronit, Andreas; Jørgensen, Sofie E.; Roed, Casper; Eriksson, Robert; Iepsen, Ulrik W.; Plovsing, Ronni R.; Storgaard, Merete; Gustafsson, Finn; Hansen, Ann-Brit E.; Mogensen, Trine H. (Frontiers in Immunology, 2021)
COVID-19 associated multisystem inflammatory syndrome (MIS) is a rare condition mostly affecting children but also adults (MIS-A). Although severe systemic inflammation and multiorgan dysfunction are hallmarks of the syndrome, the underlying pathogenesis is unclear. We aimed to provide novel immunological and genetic descriptions of MIS-A patients. Cytokine responses (IL-6, IL-1β, TNFα, CXCL10, type I, II and III interferons) following SARS-CoV-2 infection of peripheral blood mononuclear cells in vitro were analyzed as well as antibodies against IFN-alpha and IFN-omega by ELISA) in patients and healthy controls. We also performed whole exome sequencing (WES) of patient DNA. A total of five patients (ages 19, 23, 33, 38, 50 years) were included. The patients shared characteristic features, although organ involvement and the time course of disease varied slightly. SARS-CoV-2 in vitro infection of patient PBMCs revealed impaired type I and III interferon responses and reduced CXCL10 expression, whereas production of proinflammatory cytokines were less affected, compared to healthy controls. Presence of interferon autoantibodies was not detected. Whole exome sequencing analysis of patient DNA revealed 12 rare potentially disease-causing variants in genes related to autophagy, classical Kawasaki disease, restriction factors and immune responses. In conclusion, we observed an impaired production of type I and III interferons in response to SARS-CoV-2 infection and detected several rare potentially disease-causing gene variants potentially contributing to MIS-A.